2020
DOI: 10.1186/s13287-020-01625-7
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation of noncoding RNAs: new insights into osteogenesis and common bone diseases

Abstract: Bone diseases such as osteoarthritis, osteoporosis, and bone tumor present a severe public health problem. Osteogenic differentiation is a complex process associated with the differentiation of different cells, which could regulate transcription factors, cytokines, many signaling pathways, noncoding RNAs (ncRNAs), and epigenetic modulation. DNA methylation is a kind of stable epigenetic alterations in CpG islands without DNA sequence changes and is involved in cancer and other diseases, including bone developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 78 publications
(85 reference statements)
0
20
0
Order By: Relevance
“…Therefore, exploring the link between miRNAs and histone modifications may improve our understanding of HLF/OLF pathogenesis. On the other hand, DNA methylation of miRNAs has been proven to hold particular regulation function in osteogenic differentiation (Allas et al, 2019;Yu et al, 2020). For example, Li et al found that hypermethylation of miR-149 influenced the osteogenic differentiation of MSCs through SDF-1/CXCR4 signaling (Li et al, 2019).…”
Section: Microrna-based Molecular Mechanismsmentioning
confidence: 99%
“…Therefore, exploring the link between miRNAs and histone modifications may improve our understanding of HLF/OLF pathogenesis. On the other hand, DNA methylation of miRNAs has been proven to hold particular regulation function in osteogenic differentiation (Allas et al, 2019;Yu et al, 2020). For example, Li et al found that hypermethylation of miR-149 influenced the osteogenic differentiation of MSCs through SDF-1/CXCR4 signaling (Li et al, 2019).…”
Section: Microrna-based Molecular Mechanismsmentioning
confidence: 99%
“…However, screening biomarkers using changes in mRNAs only are insufficient as miRNAs, lncRNAs and the interaction between these three all play important roles in the growth and differentiation of cells and occurrence of cancers. 25,26 ceRNA hypothesis provides an in-depth understanding of the mechanism of carcinogenesis and new evidence for cancer diagnosis and treatment, chemotherapy efficacy prediction and cancer risk prediction. 6,27,28 Data mining using TCGA database is an effective approach to identify changes in RNA expression that are relevant to clinical outcomes and to screen new therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%
“…Sequencing technology and bioinformatics allow the screening of the entire DNA mutation profile and contribute to the understanding of EAC origin and characteristics. However, screening biomarkers using changes in mRNAs only are insufficient as miRNAs, lncRNAs and the interaction between these three all play important roles in the growth and differentiation of cells and occurrence of cancers 25,26 . ceRNA hypothesis provides an in‐depth understanding of the mechanism of carcinogenesis and new evidence for cancer diagnosis and treatment, chemotherapy efficacy prediction and cancer risk prediction 6,27,28 …”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation, a type of central epigenetic modi cation, is involved in diverse biological activities, including organism development, genome regulation, aging, and disease [7,8] . Methylation generally occurs on cytosine residues in cytosine-phosphate-guanine (CpG) dinucleotides [9,10] . Typically, these CpG sites are located and enriched in large clusters forming CpG islands, found mostly at the promoter regions of genes [10] .…”
Section: Introductionmentioning
confidence: 99%
“…Methylation generally occurs on cytosine residues in cytosine-phosphate-guanine (CpG) dinucleotides [9,10] . Typically, these CpG sites are located and enriched in large clusters forming CpG islands, found mostly at the promoter regions of genes [10] . The methylation of CpG islands can recruit repressive methyl-binding proteins, impair transcription factor binding, and condense chromatin structure [11,12] .…”
Section: Introductionmentioning
confidence: 99%